E o mar vai virar sertão? navegabilidade e problemas ambientais no Baixo São Francisco - Guedes, Cristiane Montalvão (2019)
The present thesis is based on the environmental impacts on the São Francisco river, in particular, on its lower section known as Baixo São Francisco. Several decades of authoritarian public policies of the governors weakened the river, which feels the difficulty of attending to the multiple uses established by Law 9.433 / 1997. From the 1970s onwards, a series of dams for hydroelectric power plants was erected along São Francisco River; to justify the modernization policy, they were linked to the "Northeast of the year 2000" and the "Brazil as a Great Power" propaganda. The objective of this work is to analyze the sense of recovery and conservation of the river adopted by the federal government, specifically in its low stretch. As one of the multiple uses of the river and having allowed in the past the traffic of large boats, navigation itself was chosen as spokesperson for São Francisco, gaining personality in a network of interactions with the river, the riverines, the NGO, the CBHSF and the governmental organs. The work is supported by the analysis of photographs, the in loco observation of stretches of the river, the documents produced by the NGO Canoas de Tolda, by the CBHSF and by governmental agencies, in the discussions during the presence in Public Audiences, and also in interviews with riverine dwellers, with boatmen e members of the NGO Canoa de Tolda. The empirical basis has contributed to the fact that the river continues to suffer from the continued intervention of governmental agencies, observed in the regularization of its flow, under the main argument of being an exit for the climate change crisis to the detriment of the lame gerenciation of the waters of the São Francisco with respect to its environmental protection; besides that the effective recovery and conservation of the river is not being put into practice, committing the waters and the people that depend of them for the survival in the Low San Francisco. What is behind the recovery and conservation of the river continues to be shaped by the interests of benefiting capitalist expansion, with noncompliance with Brazilian legislation (Law 9.433/1997).________________________________________________________________________________________________________________________________